Pengaruh Pemberian Pupuk Silika dan NPK Pada Jarak Tanam Berbeda Terhadap Pertumbuhan dan Hasil Tanaman Padi (oryza sativa l.) Varietas Ciherang - Alda Rahmatul Muslimah; Wagiono Wagiono; Darso Sugiono (Jurnal Ilmiah Wahana Pendidikan, 2021)
The silica content (Si) in the soil is decreasing, but in its repair efforts it still escapes the attention of farmers. The experiment was conducted in Experimental Station of Indonesia Center for Rice Research Sukamandi Jaua Village, Ciasem Subdistrick, West Java, from July to November 2020. The objective of the experiment was to get the best combination of silica fertilizer and NPK tailored to the plant plant spacing to increase the growth and yield of rice crops (Oryza sativa L.) Ciherang variety. The research was used experimental method it was arranged in split plot design with 8 threatments and 3 replications. As the main plot was the nurturing of NPK and silica consisting of 6 acts namely: S0 (control), S1 (100% NPK), S2 (100% NPK and 1000 kg/ha Si), S3 (75% NPK and 1000 kg/ha Si), S4 (50% NPK and 1000 kg/ha Si), S5 (100% NPK and 2000 kg/ha Si), S6 (75% NPK and 2000 kg/ha Si), and S7 (50% NPK and 2000 kg/ha Si). As subplot, the plant spacing consists of 2 treatments: P1 (25 x 25 cm) and P2 (40 x 20 x 10 cm). The results showed that there was no interaction between the combination of NPK and silica fertilizers and the plant spacing against all observation parameters. However, there was a real influence on the combination of NPK and silica fertilizer independently on plant height at 60 and 86 days after planting, the number of tillers at 60 days after planting, the number of panicles per m2, 1000 grains weight, and the grain yield. Meanwhile, in the treatment of plant spacing there was only a real influence independently on the number of tillers at 21-86 days after planting and the number of grains. Giving 100% NPK fertilizer and 1000 kg/ha silica with a plant spacing of 25 x 25 cm was the best combination because it was able to provide high yields on plant height parameters, number of tillers, 1000 grains weight and grain yield.